Motivation as a MediatingVariable in the Relationship Between Organizational Culture, Job Satisfaction, and Employee Performance at PT Musam Utjing - Hutabarat, Cindy Claudia; Suhairi, Suhairi; Jannah, Nurul (Universitas Ibn Khladun Bogor, 2025)
The plantation industry, such as palm oil, is characterized by demanding, field-based work that demands high levels of physical endurance and discipline. Therefore, work motivation is key to maintaining employee enthusiasm, perseverance, and loyalty to the company. This study applies a quantitative method. According to Sugiyono (2022), the quantitative method is rooted in the positivist paradigm, emphasizing objective measurement and statistical analysis to test hypotheses, which is applied to research specific samples or populations. The result is organizational Culture (X1) significantly influences both Work Motivation (Z) and Job Satisfaction (X2), as evidenced by a very small p-value (0.000). This indicates that a strong organizational culture can increase employee motivation and job satisfaction. On the other hand, Work Motivation (Z) also has a considerable effect on Employee Performance (Y), with a p-value of 0.001. This finding reinforces that high work motivation is closely related to improved company performance. However, the direct relationship between Organizational Culture (X1) and Company Performance (Y) does not show any statistical significance (p-value 0.051), meaning that the impact of organizational culture on performance is indirect and influenced by other variables. Furthermore, Job Satisfaction (X2) does not have a statistically significant effect on Work Motivation(Z) or Company Performance (Y), with a p-value greater than the significance level of 0.05, which implies that in this particular model, job satisfaction does not play a direct role in motivation or performance.